Expression of codon optimized HA5.1 gene with biofunctional activity in Pichia pastoris X33 - Cuong, Vo Viet; Hue, Le Thi; Huyen, Do Thi; Giang, Le Quynh; Quy, Nguyen Thi; Hai, Truong Nam (Academia Journal of Biology, 2013)
Exotic gene expression in P. pastoris is dependent on multistep processes involving regulation at the level of transcription, protein translation, and posttranslational modiﬁcations. In order to further improve the expression level of HA recombinant protein from A/H5N1 avian virus we optimized the HA5.1 protein coding sequence and expressed it in P. pastoris X33. After optimization, Codon Adaptation Index (CAI) value was improved from 0.69 to 0.98, without modifying the amino acid sequence of the encoded protein. The synthetic mha5.1 with a length of 1 kb was inserted in to pPICZαmha5.1 and cloned in E. coli DH10b then integrated into P. pastoris X33. HA5.1 recombinant protein of 50-70 kDa was synthesized at 30oC under induction of 1% methanol during 72 hours. Recombinant protein had biological function to agglutinate chicken’s blood cells at maximum 26 dilutions and had antigenicity to bind with antibody against HA5 of virus H5N1. These important results are the basis for using recombinant HA5.1 protein as a subunit vaccine.